Relationship Between Free Nutritious Food Intake (MBG) And Nutritional Status And Hemoglobin Levels In Elementary School Children In Indonesia: A Cross-Sectional Study Based On SSGI Data 2024 - Wiwit Estuti; Andri Hermawan; Retno Widyani (Jurnal Medisci, 2026)
Background: Indonesia recorded a stunting prevalence of 19.8% (SSGI 2024), down from 21.5% in 2023, but still far from the 2029 RPJMN target of 14.2%. At the same time, the prevalence of anemia in school-age children (5–14 years old) was recorded at 20.6% (Riskesdas, 2018), and in adolescents aged 15–24 years, at 15.5% (SKI, 2023). The Free Nutritious Meal (MBG) Program, launched by the government in January 2025, targets 82.9 million beneficiaries, including elementary and high school students, but its impact on nutritional status and hemoglobin levels has not been systematically measured empirically. Objective: To analyze the relationship between exposure to school feeding programs to nutritional status (z-score TB/U, BB/U, BB/TB) and hemoglobin levels of elementary school children aged 6–12 years in Indonesia, as well as identify determinants of nutrition that can be strengthened through the design of the MBG program. Methods: Quantitative research with a cross-sectional design used SSGI 2024 secondary data (n = 298,903 toddlers) combined with school-age children's supplement data from the 2023 Indonesian Health Survey (SKI). The analysis used multivariate logistic regression to identify determinants of stunting and anemia, with stratification by urban-rural area, household expenditure group, and access to government nutrition programs. Results: Children from households with access to institutional nutrition programs had a significantly lower stunting OR of 0.72 (95%CI: 0.68–0.76) and an anemic OR of 0.68 (95%CI: 0.63–0.74) compared to the group without access. Food diversity (dietary diversity score ≥5) was associated with protection against stunting (AOR 0.61; 95% CI: 0.56–0.67). The six provinces with the largest stunting burden accounted for 50% of the total national cases: West Java (638,000 children under five), Central Java (485,893), East Java (430,780), North Sumatra (316,456), NTT (214,143), and Banten (209,600). Conclusion: School-based feeding programs have significant potential to reduce the burden of stunting and anemia in school-age children, especially if they include adequate food diversity. The MBG design, which ensures that one serving meets at least 1/3 of the daily Nutritional Adequacy Rate (AKG) with iron content ≥5 mg and animal protein, can be a catalyst for accelerating stunting reduction towards the RPJMN target of 14.2% by 2029.